Classification of Lymphomas and Hematological Neoplasia in the Era of Genomic Research A Themed Issue in Honor of Dr. Elaine S. Jaffe - Nicolae, Alina; Carbone, Antonino (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue contains review articles focusing on several lymphoma entities included in the current WHO classification. The aim of the book is to guide the readers in understanding the evolution of lymphoma classification. The clinicopathological entities described in this issue have been analyzed through the molecular mechanisms involved in their pathogenesis.